By the question of the true solutions for investigation of technical problems - Draganov, B. (Енергетика і автоматика, 2015)
It sets out common concepts and the official truth. These features of the interpretation of truth in art, in literature. The focus is on the concept of truth in the laws of mathematics and physics, in evaluating the accuracy of tasks.